Análise do mercado de consumo online: uma comparação entre o Brasil e o Equador - Lamboglia, Galo Andrés Suasnavas (2017)
The following investigation aimed to understand the behavior of the online consumers in Brazil and Ecuador; in order to find the similarities or differences in their way of online shopping. Specifically, we pursued to identify buying habits and behaviors for buying process that are used by consumers in both countries; find similarities or differences in the personality traits of the online consumers of Ecuador and Brazil and in their consumption behavior; and finally, i t was sought to identify market segments of these consumers that have the same or different characteristics. In reference to the methodology, it was a quantitative research, in which it was used a semi structured questionary for data collection. This data were analyzed by descriptive statistics techniques (frequency distribution, cross tabulation, among others) and multivariate statistical techniques, as the clusters analysis. To analyze online consumers behavior there were used three theoretical models (EKB Model, The Big Five Model and The role model of the online consumer behavior). With the results we found similarities in the consumer’s behavior of both countries in the purchase decision process with small differences in certain characteristics of consu mption as the consumption of products that do not harm the environment and the frequency of post -purchase communication. In relation to the personality traits there is a noticeable difference between on line consumers in both countries, reaching to the conclusion than in Ecuador they identify the personality trait “conscientiousness” and in Brazil with “agreebleness”. In terms of market segmentation by behavior roles, both countries tend to identify as “promoter” consumers.